Synthesis-condition dependence of carbon nanotube growth by alcohol catalytic chemical vapor deposition method - Inami, Nobuhito; Mohamed, Mohd Ambri; Shikoh, Eiji; Fujiwara, Akihiko (Institute of Physics Publishing, 2007)
We report the dependence of growth yield of single-walled carbon nanotubes (SWNTs) on heat-treatment time and catalyst film thickness by the alcohol catalytic chemical vapor deposition method. Three types of heat-treatment, synthesis of 30 min, synthesis of 30 min after annealing of 30 min, and synthesis of 60 min, were investigated. Thickness of Co catalyst film was varied from 1 to 10 nm. In the case of thinner Co film less than 3 nm, long synthesis time of 60 min is favorable for the effective SWNT growth, because of the small amount of Co catalyst. In the case of thicker Co film more than 3 nm, an amount of grown SWNTs by 30 min synthesis after 30 min annealing and by 60 min synthesis was much higher than that by 30 min synthesis without annealing, showing that total heat-treatment time of 60 min is important for the SWNT growth. Results suggest that the conversion from the thicker film of Co to nano-particle which acts as catalyst takes place during the first 30 min.